Antibiotic resistance patterns of Staphylococcus spp. isolated from fast foods sold in different restaurants of Mymensingh, Bangladesh - Urmi, Monami Rahman; Ansari, Wahedul Karim; Islam, Md Saiful; Sobur, Md Abdus; Rahman, Marzia; Rahman, Md Tanvir (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: Fast foods are often responsible for staphylococcal foodborne illness. The present study was carried out to isolate Staphylococcus spp. from various fast foods sold in Mymensingh and to determine their antibiogram. Materials and Methods: Overall, 60 samples of fast foods sold in different restaurants were screened by culture, biochemical tests, and polymerase chain reaction (PCR) to isolate and identify Staphylococcus spp., followed by employing of disk diffusion method to determine their antibiotic resistance patterns. Results: Among these 60 samples, 8 [13.33%, 95% confidence interval (CI): 6.91%–24.17%] were positive for Staphylococcus spp. by cultural and biochemical properties. By PCR, four (6.67%, 95% CI: 2.62%–15.93%) isolates were confirmed as Staphylococcus aureus by targeting nuc gene. Additionally, all the S. aureus isolates were coagulase-positive. By antibiogram profiles, all the Staphylococcus isolates exhibited resistance to azithromycin and erythromycin (95% CI: 67.56%– 100.00%), and frequently resistance to cefixime (75%, 95% CI: 40.93%–95.56%), ampicillin (50%, 95% CI: 21.52%–78.48%), and amoxicillin (37.5%, 95% CI: 13.68%–69.43%); moderate to lower resistance was found against cefotaxime, gentamicin, and doxycycline. In addition, all the isolates were sensitive to ciprofloxacin and chloramphenicol. Interestingly, 75% (6/8; 95% CI: 40.93%– 95.56%) isolates were multidrug-resistant (MDR) in nature. Furthermore, the indices of multiple antibiotic resistance (MAR) were ranged from 0.2 to 0.6. Conclusion: This study revealed that fast foods sold in restaurants were contaminated with MDR and MAR Staphylococcus isolates, having potential public health significance. J. Adv. Vet. Anim. Res., 8(2): 274-281, June 2021